Just the two of us : human-object relationships in consumer culture - Lai, Junjie (2012)
Shopping has become an activity for identity-construction, where the consumer objects that one purchases has the potential to shape identity. My paper seeks to examine the link between consumer habits and one's sense of identity as shaped by objects, through an analysis of consumer habits and choices, and how people develop relationships with consumer objects over time. A total of 12 in-depth interviews were conducted with young, unmarried Singaporeans. Findings generally show that respondents went through several common stages during the development of relations with consumer objects. These stages were broadly categorised as: (i) Shop spaces that orient the shopping experience and mitigate meanings, (ii) Creation of meaning towards objects prior to purchase and ownership, (iii) Meaning-making and object- relations after purchase and (iv) Long term relations with the object. The study concludes that consumer culture and human-object relations have multi-faceted and complex effects on human identity.